It is neither.
To be even, f(x) must equal f(-x).
If you substitute -x for x, you'd get
y = (-x)^2 - 2(-x) -8
y = x^2 +2x -8
This is not the same as the original, so this is not even.
To be odd, f(x) must equal -f(-x).
If you take the -x substitution from the last step and then multiply it by -1, you'd have:
y = -1 (x^2 +2x -8)
y = -x^2 -2x +8
This is not the same as the original either.
The function is neither even nor odd.
Answer:
x = 4
y = 11
Step-by-step explanation:
Set your formula as follow:
2x+3=3x-1 -> 2x+3-3x=-1 -> -x+3 = -1 -> -x=-4 -> x=4
now substitute x for 4 in the following
y-2=2(4)+1 -> y-2=8+1 ->y-2 = 9y -> y=11
Part one of answering how to factor
Answer:
A positive correlation on a scatter plot would show the points closer tog.ether heading in an upward direction
Step-by-step explanation: